2014
DOI: 10.1007/s00134-013-3194-3
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning reduces mortality from acute respiratory distress syndrome in the low tidal volume era: a meta-analysis

Abstract: Purpose Prone positioning for ARDS has been performed for decades without definitive evidence of clinical benefit. A recent multicenter trial demonstrated for the first time significantly reduced mortality with prone positioning. This meta-analysis was performed to integrate these findings with existing literature and test whether differences in tidal volume explain conflicting results among randomized trials. Methods Studies were identified using MEDLINE, EMBASE, Cochrane Register of Controlled Trials, LILA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 52 publications
2
155
0
13
Order By: Relevance
“…Meta-analysis including this study demonstrated reduced mortality in patients treated with prone compared with supine position (RR 0.85; 95% CI 0.71-1.01) as well as improved oxygenation as measured by change in Pao 2 /Fio 2 ratio (median 24.03 higher, 95% CI 13.3-34.7 higher) [375]. Most patients respond to the prone position with improved oxygenation and may also have improved lung compliance [374,[376][377][378][379].…”
Section: We Suggest Using Recruitment Maneuvers In Adult Patients Witmentioning
confidence: 64%
See 1 more Smart Citation
“…Meta-analysis including this study demonstrated reduced mortality in patients treated with prone compared with supine position (RR 0.85; 95% CI 0.71-1.01) as well as improved oxygenation as measured by change in Pao 2 /Fio 2 ratio (median 24.03 higher, 95% CI 13.3-34.7 higher) [375]. Most patients respond to the prone position with improved oxygenation and may also have improved lung compliance [374,[376][377][378][379].…”
Section: We Suggest Using Recruitment Maneuvers In Adult Patients Witmentioning
confidence: 64%
“…While prone position may be associated with potentially life-threatening complications including accidental removal of the endotracheal tube, this was not evident in pooled analysis (RR 1.09; 95% CI 0.85-1.39). However, prone position was associated with an increase in pressure sores (RR 1.37; 95% CI 1.05-1.79) [375], and some patients have contraindications to the prone position [374].…”
Section: We Suggest Using Recruitment Maneuvers In Adult Patients Witmentioning
confidence: 99%
“…Thus, prone positioning might be considered a recruitment maneuver. 46 One randomized controlled trial 47 and several meta-analyses report a survival benefit for prone position, 48,49 particularly in severe ARDS. 43 …”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…Below the timeline are other important trials and meta-analyses in ARDS. 3,4,7,9,18,21,22 PP ϭ prone positioning, LPV ϭ lungprotective ventilation, NR ϭ not reported, NMB ϭ neuromuscular blockade, RR ϭ relative risk, RCT ϭ randomized controlled trial. *, reported only as a complication as a percentage of subjects who needed increased sedation/muscle relaxants after protocol initiation.…”
Section: Prone Positioning As a Standard For Ards-promentioning
confidence: 99%